Effectiveness of the Mindfulness in Schools Programme: non-randomised controlled feasibility study. - Kuyken, W; Weare, K; Ukoumunne, O; Vicary, R; Motton, N; Burnett, R; Cullen, C; Hennelly, S; Huppert, F (2013)
BACKGROUND: Mindfulness-based approaches for adults are effective at enhancing mental health, but few controlled trials have evaluated their effectiveness among young people. AIMS: To assess the acceptability and efficacy of a schools-based universal mindfulness intervention to enhance mental health and well-being. METHOD: A total of 522 young people aged 12-16 in 12 secondary schools either participated in the Mindfulness in Schools Programme (intervention) or took part in the usual school curriculum (control). RESULTS: Rates of acceptability were high. Relative to the controls, and after adjusting for baseline imbalances, children who participated in the intervention reported fewer depressive symptoms post-treatment (P = 0.004) and at follow-up (P = 0.005) and lower stress (P = 0.05) and greater well-being (P = 0.05) at follow-up. The degree to which students in the intervention group practised the mindfulness skills was associated with better well-being (P<0.001) and less stress (P = 0.03) at 3-month follow-up. CONCLUSIONS: The findings provide promising evidence of the programme's acceptability and efficacy.